(untitled) (Romanian Journal of Analytic Philosophy, 2025)
Thomas Nagel’s end note of his famous essay “What is it like to be a bat?” introduced the speculative proposal of developing an objective phenomenology capable of enabling further empirical studies of consciousness. I will argue that such an endeavor inevitably faces two major difficulties in the first-order inaccessible qualia and second-order inaccessible qualia. The latter essentially comprise all of our qualitative contents associated with our experiences, as all qualia are private or inaccessible by other agents who do not share the same point of view, while the former should be seen as a subgroup of phenomenal contents that are temporarily or permanently unconscious or, more explicitly, unavailable to the agent to whom they belong to.